2012
DOI: 10.1002/jssc.201200528
|View full text |Cite
|
Sign up to set email alerts
|

Structure selective complexation of cyclodextrins with five polyphenols investigated by capillary electrokinetic chromatography

Abstract: The complexation of five polyphenols, namely trans-resveratrol, astilbin, taxifolin, ferulic acid, and syringic acid (guest molecules) with α-, β-, and γ-cyclodextrin (host molecules), was investigated by capillary electrokinetic chromatography. The binding constants were calculated based on the effective electrophoretic mobility change of guests with the addition of cyclodextrins into the background electrolyte. Because of cavity size, cyclodextrins showed structure-selective complexation property to differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…Increases in T have been explicitly demonstrated to increase the aqueous solubility of sparingly soluble polyphenols in the presence of various cyclodextrins [39]. On the other hand, it was found that the binding constants of certain polyphenol complexes with α-, β-, and γ-cyclodextrin decreased as T increased [40]. Results on the interactions of the stilbene (E)-piceatannol with HP-β-CD were in concurrence, illustrating a decrease in the complexation constant as a response to increasing T [41].…”
Section: The Effect Of Ph Regulationmentioning
confidence: 99%
“…Increases in T have been explicitly demonstrated to increase the aqueous solubility of sparingly soluble polyphenols in the presence of various cyclodextrins [39]. On the other hand, it was found that the binding constants of certain polyphenol complexes with α-, β-, and γ-cyclodextrin decreased as T increased [40]. Results on the interactions of the stilbene (E)-piceatannol with HP-β-CD were in concurrence, illustrating a decrease in the complexation constant as a response to increasing T [41].…”
Section: The Effect Of Ph Regulationmentioning
confidence: 99%
“…To determine stability constants and thermodynamic parameters, a number of techniques are used [6,7], including UV-Vis [8][9][10] and fluorescence [8,9,11] spectroscopy, conductometry [12,13], isothermal calorimetry [14][15][16][17], phase solubility study with UV-Vis spectroscopy [14,18,19] or high-performance liquid chromatography [20], potentiometry [21], capillary electrophoresis [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], and other techniques. Capillary electrophoresis (CE) has advantages such as rapidity, high selectivity, a small value of samples, and low-cost of analysis.…”
Section: Introductionmentioning
confidence: 99%
“…32 On the other hand, synthetic macrocyclic host compounds, [33][34][35][36][37][38] such as crown ethers, cyclodextrins, calixarenes, and cucurbiturils, play important roles in supramolecular chemistry and nanoscience, and receive considerable attention as adsorption materials in recent years. [39][40][41][42] Pillarenes (or pillararenes), 43 a new class of supramolecular hosts which were rstly synthesized in 2008, 44 have become one of the most popular topics in supramolecular chemistry. [45][46][47][48][49][50][51][52][53][54][55][56][57][58] Recently, we successfully employed carboxylatopillar [5]arenes (CP [5]As) 59 as sorbent materials, either by functionalizing them on the surface of Fe 3 O 4 magnetic nanoparticles via covalent bonds for the extraction and detection of pesticides 60 or by packing them in a glass microcolumn for the separation and preconcentration of trace gold and palladium via ow injection ame atomic absorption spectrometry.…”
Section: Introductionmentioning
confidence: 99%